Towards a European reassessment of punitive law enforcement?: valedictory lecture = Naar een Europese herijking van het punitief handhavingsrecht? : rede uitgesproken ter gelegenheid van zijn afscheid als hoogleraar economisch en Europees strafrechtaan de Universiteit Utrecht op 10 maart 2023 - Vervaele, John A. E. (Pompe reeks, 2023)
"The European Union is today a major player in many policy areas, going from classic economic fields as competition policy, agriculture and fisheries policy to new emergent fields as environmental policy, arterial intelligence policy, security and foreign policy and criminal justice policy. These policies comes with an increasing level of EU regulation, having also a substantive impact on the harmonization of national policies and regulations. This expansion of EU competence naturally also places new demands on their enforcement, especially when it comes to investigations with the aim of imposing punitive administrative and/or criminal sanctions. In this expanded version of his valedictory lecture Prof. Vervaele is assessing 1) to what extent the EU and its Member States have a policy on punitive enforcement in the internal market and in the Area of Freedom Security and Justice and 2) how this policy translates into the harmonization of substantive administrative and criminal law and procedural law at the national level and into the elaboration of administrative and judicial cooperation instruments and the setting up of European enforcement agencies. The assessment includes to what extent this policy takes account of the human rights obligations. Vervaele concludes with a plea for a European model for punitive law enforcement with an increased alignment between the administrative enforcement tools in the internal market and the criminal enforcement tools in the Area of Freedom, Security and Justice. In this model the national enforcement authorities are build in under a network cooperation scheme."--